Desempenho operacional e energético de colhedoras de cana-de-açúcar ( Saccaharum spp.) para uma e duas linhas da cultura - Testa, João Vitor Paulo [UNESP] (2014)
Brazil is the largest producer of sugarcane ( Saccharum spp.) In the world, so its cultivation is of great importance for the Brazilian agribusiness. Harvest mechanization of sugarcane became necessary because the burning of field is gradually being banned in Brazil and, without this practice, manual cutting becomes inefficient and costly. With the increase of mechanized harvesting innovations in the sector appeared to increase the performance of this operation and, in recent years, the attempt to develop a specify harvester for two rows simultaneous became reality. The objective of this study was to evaluate the operational and energy performance of two harvesters of sugarcane for one and two lines of planting. The tests were conducted on a sugarcane field harvested without burning, the variety RB855156 in his second cut, with spacing of 1.5 m between lines, estimated agricultural productivity of 83.5 t ha -1 and plants upright. The experiment was divided into two stages: in the first, machines were evaluated in three forward speeds (2.5 km h -1 3.5 km h -1 and 5 km h -1 ) and the second stage were selected normal working speeds for models of one and two ...